Nano‐omics: Frontier fields of fusion of nanotechnology - Xuan Wang; Weichen Xu; Jun Li; Chen Shi; Yuanyuan Guo; Jinjun Shan; Ruogu Qi (Smart Medicine, 2023)
Abstract Nanotechnology, an emerging force, has infiltrated diverse domains like biomedical, materials, and environmental sciences. Nano‐omics, an emerging fusion, combines nanotechnology with omics, boasting amplified sensitivity and resolution. This review introduces nanotechnology basics, surveys its recent strides in nano‐omics, deliberates present challenges, and envisions future growth.